Factores de riesgo perinatales asociados a fractura de clavícula en recién nacidos - Ticona Rendón, Manuel Benedicto (2021)
Objective: To determine the prenatal and neonatal factors associated with neonatal clavicle fracture. Material and methods: Analytical study of cases and controls carried out at the Hospital II René Toche Groppo of EsSalud, in Chincha, Ica-Perú, from January 2018 to October 2019. 36 cases were found and 108 controls were taken at random, the data were obtained from the review of medical records, for the analysis odds ratio was used with 95 % confidence interval and p value considering risk factor when p < 0.05 and 95 % CI is greater than 1. Results: The prevalence of neonatal clavicle fracture was 1.4 %, with predominance of the right side (83.3 %). The prenatal and obstetric factors that were associated were: primiparity and presence of funicular dystocia (OR: 2.89; CI: 1.20-6.88; p: 0.015, respectively). Neonatal factors were: birth weight greater than 3800 grams (OR: 2.49; CI: 1.10-5.63; p: 0.026). Conclusion: Risk factors associated with clavicle fracture were primiparity, funicular dystocia and birth weight > 3800 g.